Nature’s way-our way: A journey through the co-creation and sharing of an Indigenous physical literacy enriched early years initiative - Amanda Froehlich Chow; Kathy Wahpepah; Louise Humbert; Natalie Houser; Mariana Brussoni; Marta Erlandson; Amanda Gannon; Ashley Larmour; Erica Stevenson; Kathryn Riley; Fatima Ali (Engaged Scholar Journal)
Early years are a critical time in the healthy development of young children. It is essential for children to develop healthy bonds with family members to increase well-being. Colonialism has resulted in the loss of many Indigenous activities, intergenerational teachings and relationship-building strategies that encourage wholistic health-promoting behaviours. Research focused on physical activity behaviours among early years children has had limited success. To address these challenges, the Western concept of physical literacy that applies a wholistic approach to physical activity by focusing on physical, social, emotional, and spiritual wellness can align with many Indigenous Ways of Knowing, Being and Doing.